2019
DOI: 10.26832/24566632.2019.0401015
|View full text |Cite
|
Sign up to set email alerts
|

Current status of bacterial contamination in some fish species of Bakkhali river Estuary, Bangladesh

Abstract: The present study aims to investigate the isolation of human pathogenic bacteria (Escherichia coli, Salmonella spp. Shigella spp. and Vibrio spp.) and in gills, intestines, skin of fishes of Bakkhali River Estuary, Cox's Bazar. A total of 50 fish species (25 of Pomadasys hasta and 25 of Glossogobius giuris) were collected from two sampling stations namely Station-1 (Rumalia Chara) and Station-2 (Kusturi Ghat). Bacterial analyses were made by standard methods. Total heterotrophic bacterial load of the isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Okonkwo et al [23] did not isolate any Vibrio species from crab samples in their findings; a result which supported absolutely with the result gotten from this findings. Vibrio cholerae reported by Jahan et al [24] supported the findings from this study as two V. cholerae were identified from fish samples. No Vibrio species was isolated from shrimp samples in their findings, an outcome which was parallel to Okonkwo et al [23].…”
Section: Discussionsupporting
confidence: 91%
“…Okonkwo et al [23] did not isolate any Vibrio species from crab samples in their findings; a result which supported absolutely with the result gotten from this findings. Vibrio cholerae reported by Jahan et al [24] supported the findings from this study as two V. cholerae were identified from fish samples. No Vibrio species was isolated from shrimp samples in their findings, an outcome which was parallel to Okonkwo et al [23].…”
Section: Discussionsupporting
confidence: 91%
“…The presence of S. aureus and CNS means that the fish were contaminated from human and animal wastes at the source (lake) or during handling. In this study, there was no Salmonella , Listeria , Vibrio , and Shigella genera, which were isolated by [3, 4, 16, 20]. In our study, we isolated more bacteria genera (8) than that in [3, 4, 16, 20].…”
Section: Discussionmentioning
confidence: 52%
“…There is also a problem of bursting of sewage pipes, thus exuding raw untreated sewage from the high-density suburbs. Fish are contaminated from the sewage and industrial wastes [20] as well as from poor handling techniques by vendors.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the bacterial count on the skin surface of Etroplus suratensis collected from upstream and downstream regions of the Mogral river in Kasargod, Kerala was 4.41 and 4.92 log CFU g -1 respectively (Megha and Harikumar, 2016). Jahan et al (2019) showed that the bacterial count on the surface of the fish, which varied with the species and the source, ranged from 3.5 to 5.17 log CFU g -1 .…”
Section: Discussionmentioning
confidence: 99%